2007
DOI: 10.3171/jns.2007.106.6.994
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhage after particle embolization of hemangioblastomas: comparison of outcomes in spinal and cerebellar lesions

Abstract: The authors no longer use particle embolization to treat cerebellar hemangioblastomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 15 publications
0
62
0
Order By: Relevance
“…Several available published data also showed that preoperative embolization was a safe and effective adjuvant therapy (Djindjian, 1986;Standard et al, 1994;Krishnan et al, 2006;Cornelius et al, 2007;Agrawal et al, 2010). However, the reports of preoperative embolization of CHB are still relatively rare, and most of them were individual case reports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several available published data also showed that preoperative embolization was a safe and effective adjuvant therapy (Djindjian, 1986;Standard et al, 1994;Krishnan et al, 2006;Cornelius et al, 2007;Agrawal et al, 2010). However, the reports of preoperative embolization of CHB are still relatively rare, and most of them were individual case reports.…”
Section: Introductionmentioning
confidence: 99%
“…A large comparative study of the CHB surgical treatment with and without preoperative embolization remains lacking. Therefore, to the extent that we know, the safety and effectiveness of preoperative embolization in CHB treatment has yet to be confirmed (Standard et al, 1994;Krishnan et al, 2006;Cornelius et al, 2007). A study that compares surgical time, intraoperative blood loss and blood transfusion, clinical efficacy and incidence of complications between patients underwent surgical resection with and without preoperative embolization is essential to evaluate the risk and benefits of preoperative embolization in the surgical treatment of CHB.…”
Section: Introductionmentioning
confidence: 99%
“…Cornelius et al 24 summarized several studies on preoperative embolization and reported an embolization-related complication rate of 5.6% in patients with spinal hemangioblastomas. Shi et al 86 reported no complications after embolization in 18 cases of vascular spinal tumors.…”
Section: 43mentioning
confidence: 99%
“…24,32,77 Spinal cord ischemia due to inadvertent vessel embolization of unrecognized radiculomedullary arteries is a devastating possible complication. 48,72 Other reported complications have included pain, and subarachnoid, peritumoral hemorrhage.…”
Section: Procedure-related Complicationsmentioning
confidence: 99%
See 1 more Smart Citation